Arrhythmogenic right-ventricular cardiomyopathy with plakophilin-2 genetic variant concomitant with early manifestation of ventricular tachyarrhythmia: a case series. Issue 10 (23rd September 2022) - Kawano, Kyoko; Kondo, Hidekazu; Takahashi, Masaki; Shinohara, Tetsuji; Ohno, Seiko; Horie, Minoru; Takahashi, Naohiko
Abstract: Background: Arrhythmogenic right-ventricular cardiomyopathy (ARVC) is a hereditary cardiomyopathy characterized by fibro-fat replacement of the right-ventricular myocardium. There are many factors associated with poor prognosis in patients with ARVC. Among these factors, intensive physical exertion is considered an important risk factor for sudden cardiac death. Case summary: Herein, we report a case series of siblings with ARVC and an early manifestation of ventricular tachyarrhythmia. Plakophilin-2 (PKP2) genetic variant, which is one of the causative genetic variants of ARVC, was detected by genetic testing in all three siblings. They were young athletes with lethal/symptomatic ventricular tachycardias. The eldest sibling was implanted with a transvenous implantable cardioverter defibrillator (ICD) due to resuscitated cardiopulmonary arrest at 18 years of age; the next oldest patient was treated with successful catheter ablation at 17 years; the youngest patient was treated with catheter ablation and subcutaneous ICD implantation at 17 years. Discussion: A recent experimental model revealed that physical exertion in PKP2 knockout mice diminished cardiac muscle mass and increased cardiac myocyte apoptosis, despite enhanced arrhythmogenicity such as increased fractional shortening and calcium transient amplitude. The three siblings were heterozygous for the previously reported pathologic splice site variant c.2489 + 1G > A in Intron 12 of the PKP2. The variant might play an important role in facilitating the vulnerability to arrhythmia under intensive endurance training. Most ARVC patients with PKP2 variant, especially pathologic splice site variant c.2489 + 1G > A in Intron 12 of the PKP2, might have to be managed strictly regarding daily exercise.